UANG SEBAGAI PENGGANTI HEWAN QURBAN: KAJIAN FIQH KONTEMPORER - Dintara Lubis, Syaddan; Iqbal Irham, Muhammad; Faisal Hamdani, Muhammad (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The tradition of qurban in Islam according to sharia is realized through the slaughter of livestock as a form of approaching Allah and social solidarity. However, in modern developments, a form of qurban diversion has emerged from animal slaughter to cash transfer to those in need. This study aims to analyze the phenomenon of "cash qurban" from a contemporary fiqh perspective. Through a qualitative descriptive approach with a literature study method, this study explores the views of classical and contemporary scholars regarding the validity of this form of qurban diversion in a modern context. The results of the study show that although according to sharia qurban has symbolic and ritual dimensions attached to animal slaughter, there is room for ijtihad under certain conditions. For the 19th century tafsir scholar Sheikh As-Sa'di, the purpose of qurban can be achieved by spending some of one's wealth (maal), although it still raises debate, especially regarding the essence of qurban, intention, and the sustainability of its spiritual value. This study recommends a moderate approach that considers the interests of the community, without ignoring the basic principles of qurban worship in Islam.